The Administrative Judiciary Reforms in Young Democracy Countries (Comparative Legal Analysis) - Krawczyk, Agnieszka (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The study is the result of a legal comparative analysis of the directions of reforms in the administrative judiciary in the countries of young democracy: Poland, the Czech Republic, Lithuania, Croatia, Serbia, Hungary, Ukraine, Georgia and Kazakhstan. The analysis was carried out with reference to the patterns developed in old European democracies, mainly in Austria and Germany. Papers on reforms of the administrative judiciary in each of these countries were delivered at the international scientific conference: Reforms of administrative judiciary in the countries of young democracy (10–11.06.2021, Faculty of Law and Administration, University of Lodz). They focused on three issues: 1) contemporary challenges of the rule of law and administrative judiciary, 2) directions of changes in the national systems of administrative judiciary, 3) the future of administrative judiciary. The content of the study refers to this system of issues, which reflects the stages of development of administrative judiciary in the countries of young democracy. The conclusions drawn from the analysis show the results of reforms at each of these stages – from the constitutionalization of the rule of law, through the independence of the court-administrative procedure, to the stage of the present, extremely difficult challenges, not only of a procedural nature.